Taxonomic Organization of the Family Brucellaceae Based on a Phylogenomic Approach - Leclercq, Sébastien O.; Cloeckaert, Axel; Zygmunt, Michel S. (Frontiers in Microbiology, 2020)
Deciphering the evolutionary history of pathogenic bacteria and their near neighbours may help to understand the genetic or ecological bases which led to their pathogenic behaviour. The Brucellaceae family comprises zoonotic pathogenic species belonging to the genus Brucella as well as the environmental genus Ochrobactrum for which some species are considered as opportunistic pathogens. Here, we used a phylogenomic approach including a set of 145 Brucellaceae genomes representative of the family diversity and more than 40 genomes of the order Rhizobiales to infer the taxonomic relationships between the family’s species. Our results clarified some unresolved phylogenetic ambiguities, such as the exclusion of Mycoplana spp. out of the family Brucellaceae and the positioning of all Brucella spp. as a single genomic species within the current Ochrobactrum species diversity. Additional analyses also revealed that Ochrobactrum spp. separate into two clades, one comprising mostly environmental species while the other one includes the species considered as pathogens (Brucella spp.) or opportunistic pathogens (mainly O. anthropi, O. intermedium, and O. pseudintermedium). Finally, we show that O. intermedium is undergoing a beginning of genome reduction suggestive of an ongoing ecological niche specialization, and that some lineages of O. intermedium and O. anthropi may shift toward an adaption to the human host.